مسرح الطفل ودوره في معالجة بعض قضايا المستحدثات العلمية والتكنولوجية والقيم الأخلاقية المرتبطة بها: دراسة تحليلية على نماذج مسرحية مختارة - بخيت، أحمد السيد أحمد (جامعة بنها - كلية التربية, 2022)
مشكلة البحث 1- ما المستحدثات العلمية والتكنولوجية، ومجالاتها التطبيقية؟ 2- ما الفوائد الناتجة عن استخدامات المستحدثات العلمية والتكنولوجية؟ أهمية البحث 1- بالرغم من وجود عدد من الأبحاث والدراسات التي تناولت دور مسرح الطفل في تنمية الوعي بالقيم الأخلاقية إلا أنها لم تلقى اهتماما بعلاقته بالمستحدثات العلمية والتكنولوجية ولعل قلة البحوث والدراسات العلمية في هذا المجال أعطى للبحث الحالي قيمة ودورا مهما وفعالا. 2- يعد البحث الحالي استجابة لتوصيات العديد من الأبحاث والدراسات العربية والأجنبية التي نادت بضرورة تنمية وعي الأطفال بالمستحدثات العلمية والتكنولوجية والقيم الأخلاقية المرتبطة بها لموكبة التطورات العلمية الحديثة. أهداف البحث 1- تسليط الضوء على المستحدثات العلمية والتكنولوجية باعتبارها من الموضوعات التخصصية ذات الأهمية البالغة في حياة الطفل وثقافته. 2- الكشف عن القيم الأخلاقية المرتبطة بالمستحدثات العلمية والتكنولوجية وتعميق فهم الأطفال كمطلب من متطلبات التربية والإعداد للمستقبل. منهج البحث: يعتمد الباحث على المنهج الوصفي التحليلي لمجموعة عمدية من نصوص مسرح الطفل. عينة البحث: شملت عدد ثلاث نصوص مسرحية هي 1- الأم الخشبية تأليف نبيل خلف كتبت عام 1999م 2- فراشة الأميرة الحمراء تأليف نبيل خلف كتبت عام 2000م 3- أسعد سعيد في العالم تأليف محمود عامر كتبت عام 2007م نتائج البحث 1- تنوعت المستحدثات العلمية والتكنولوجية التي تناولها البحث فشملت تكنولوجيا الإنترنت عبر الحاسب الآلي والتليفون المحمول- الهندسة الوراثية- إنتاج الكائنات الحية المهندسة وراثيا- الاستنساخ- زراعة الأعضاء البشرية- الأمهات البديلات (تأجير الأرحام)- الطاقة النووية- بنوك الأجنحة المجمدة- مشروع الجينوم البشري مما يدل على سعة ثقافة المؤلف واطلاعه على العديد من الكتب والمراجع العلمية. Research problem 1. What are the scientific and technological innovations, and their application fields? 2. What are the benefits resulting from the use of scientific and technological innovations? research importance 1. Although there are a number of researches and studies that dealt with the role of children’s theater in developing awareness of moral values, they did not receive attention in relation to scientific and technological innovations. Perhaps the lack of research and scientific studies in this field gave the current research an important and effective role. 2. The current research is a response to the recommendations of many Arab and foreign researches and studies that called for the need to develop children's awareness of scientific and technological innovations and the ethical values associated with them to keep pace with modern scientific developments. research aims 1. Shedding light on scientific and technological innovations as they are of the most important specialized topics in the life and culture of the child. 2. Uncovering the moral values associated with scientific and technological innovations and deepening the understanding of children as a requirement of education and preparation for the future. Research Methodology The researcher relies on the descriptive analytical method for a deliberate group of child theater texts. The research sample: It included a number of three theatrical scripts: 1. The Wooden Mother, written by Nabil Khalaf, written in 1999 2. The Red Princess Butterfly, written by Nabil Khalaf, written in 2000 AD 3. The happiest Saeed in the world, written by Mahmoud Amer, written in 2007 research results 1. The various scientific and technological innovations covered by the research included internet technology via computers and mobile phones- genetic engineering- production of genetically engineered organisms- cloning- human organ transplantation- surrogates (surrogacy)- nuclear energy- frozen wing banks- human genome project Which indicates the capacity of the author's culture and his knowledge of many books and scientific references.
Keywords: القيم الأخلاقية -- المستحدثات العلمية -- النصوص المسرحية -- أدب الأطفال